Development of a herpes zoster vaccination intention scale and identification of factors associated with vaccine hesitancy among middle-aged and older attendees in community health centers: A Protection Motivation Theory based study - Ying Gao; Ting Wei; Ruijie Gong; Linfei Cai; Yuhui Sheng; Meili Shang; Yang Ni (Human Vaccines & Immunotherapeutics)
Herpes zoster (HZ) vaccination remains underutilized in China despite its increasing disease burden. Psychological drivers of HZ vaccine hesitancy are not well understood. This study aimed to explore the socio-demographic and psychological factors associated with HZ vaccine hesitancy among community health center attendees using a Protection Motivation Theory (PMT) framework. This study aimed to examine the associations between socio-demographic factors, PMT constructs, and HZ vaccine hesitancy among community health center attendees.A cross-sectional survey was conducted in Shanghai, China, from October to December 2022. Participants aged 40 years or older were recruited from seven community health centers (CHCs). Vaccine hesitancy was defined as participants who had neither received the HZ vaccine nor expressed intention to receive it. Data on socio-demographic characteristics, health behaviors and vaccine hesitancy were collected using a structured questionnaire. A PMT-based HZ vaccination intention scale consisting of five dimensions (Intrinsic Rewards, Extrinsic Rewards, Self-Efficacy, Response Efficacy, and Response Costs) was developed. Group comparisons between the vaccine hesitancy and non-hesitancy groups were made using the Mann-Whitney U test for continuous variables and the chi-square test for categorical variables. Logistic regression was used to identify factors associated with vaccine hesitancy, and a nomogram was constructed to summarize these associations. Receiver operating characteristic (ROC) analysis was performed to assess the degree of association between the PMT dimensions and vaccine hesitancy.Among 1,492 participants (median age 53; 64.2% female), 80.5% of participants reported HZ vaccine hesitancy. Hesitancy was significantly associated with older age, peri-urban residence, employment and no history of HZ infection (p < .01). Among the PMT dimensions, lower Self-Efficacy (p=0.025), higher Response Costs (p < .001), and stronger Intrinsic Rewards (p = .002) and Extrinsic Rewards (p < .001) significantly contributed to hesitancy, while Response Efficacy (p = .230) showed no clear association. The adjusted multivariate logistic regression model had an area under the curve (AUC) of 0.788, with Self-Efficacy and Extrinsic Rewards showing notable individual contributions (AUC = 0.713 and 0.696, respectively).HZ vaccine hesitancy is shaped by psychological and contextual factors. Public health strategies should prioritize perceived rewards, self-efficacy, and response costs. The tools developed in this study may guide targeted interventions in primary care. Future research should validate them across populations and assess their predictive utility in real-world settings.